Nature and Heterogeneity of the Antigens of Neisseria gonorrhoeae Involved in the Serum Bactericidal Reaction - Glynn, A. A. (1970)
Sixty strains of Neisseria gonorrhoeae have been classified into four main groups according to their resistance to killing by human complement together with either normal human or immune rabbit antibodies. The rabbit antisera had been raised against 10 of the strains tested. The normal human antibodies had probably been formed against cross-reacting organisms since they could be removed by absorption with N. pharyngis sicca, N. pharyngis flavus, N. catarrhalis, or Escherichia coli. Bactericidal antibodies could be absorbed from both normal and immune sera by N. gonorrhoeae which had been autoclaved or trypsinized, and by red cells coated with gonococcal lipopolysaccharides. The results suggest that the antigens involved in the bactericidal reaction are lipopolysaccharides of several distinct specificities. Since individual sera always reacted more widely in hemagglutination than in bactericidal tests, it is postulated that surface-blocking antigens may restrict access to the lipopolysaccharides in the intact organisms.